Organised crime in Latin America: an introduction to the special issue - Zaitch, Damián (Trends in organized crime, 2019)
This article provides an introduction to the articles submitted to the special issue of Trends in Organised Crime on ‘Organised Crime in Latin America’. The aim of the special issue is to draw together novel empirical research findings and theoretical accounts on various aspects of organised crime in the particular geographic context.